Centering Indigenous People in the Study of Religion in America - Hale, Tiffany (Numen, 2020)
This essay considers Jennifer Graber’s The Gods of Indian Country and Pamela Klassen’s The Story of Radio Mind together in considering new developments in the field of Native American and Indigenous studies. Hale examines how these books discuss the role of religion in shaping settler colonialism in North America in the nineteenth and early twentieth centuries. She concludes that both works raise pressing methodological questions about how historians of religion can center the lives of Native American people in their work.